Analysis of the corn industry in Mindanao - Shuck, Vlademir A.
This study is an analysis of the Mindanao corn industry. Specifically, it aimed to:(1) examine the dimensions of the demand and supply of corn; (2) analyze the potential increase in the domestic demand for corn by the hog and animal feed industry as an offshoot of an increasing price of wheat; (3) measure the rate of substitutability of corn to wheat in the production of animal feeds; (4) determine the elasticity for the demand and supply of corn; and (5) identify and explain policy implications that may arise from the results of the study. Secondary data were used in analyzing; production efficiency, product quality and quantity, price of corn, labor and income, substitutability of corn to wheat, the effect of peso-dollar exchange rate, the role of the public and private sector, and the impact of globalization. The results of the study show that the total demand for domestic corn was greatly influenced by the Mindanao GRDP (Gross Regional Domestic Product) income, price of corn and price of wheat. Conversely, demand for corn used as feeds is affected by the changes in the price of chicken, and price of cattle. Total domestic supply for corn was greatly determined by the area harvested for corn and the salary for corn farmers. Globalization is the biggest challenge that the Mindanao corn industry is facing. The importation of enormous volume of corn substitutes in the Philippines is directly or indirectly killing the local corn industry. Thus, there is a need to review and reconsider priority concerns on policies regarding the agricultural sector. Existing government programs such as the "Ginintuang Masaganang Ani for Corn" and the Grains Highway must be reinforced with strict policy implementation. Furthermore, the corn farmers must be empowered by providing seminars and trainings, which will equip them with better technology for efficient corn production.